Thin-film Al0.30Ga0.70As (111) as a ‘flat’ source of high-purity orthogonally polarized entangled photons - Stich, Simon; Sultanov, Vitaliy; Blaikie, Trevor; Shi, Qingyu; Wasilewski, Zbig; Belkin, Mikhail A.; Chekhova, Maria (Optics Express, 2026)
Flat-optics platforms offer new opportunities for the generation of entangled photons by relaxing traditional phase-matching constraints, enabling the use of a broader range of nonlinear materials. Among these, gallium arsenide and aluminum gallium arsenide stand out for their exceptionally high second-order nonlinearities, but their conventional orientation (001) has limited their applicability for photon-pair generation. By transitioning to crystals with (111) surface orientation, we overcome these limitations. We demonstrate a flat-optics-based telecom-range SPDC source using Al0.30Ga0.70As that achieves a high photon-pair generation rate per pump power and bandwidth of up to 0.24 Hz/mW/nm. The choice of 30% aluminum concentration allowed us to reduce pump absorption and photoluminescence background for photon pairs generation at telecom wavelengths by at least an order of magnitude compared to that of GaAs. The specific layer orientation facilitates the generation of orthogonally polarized entangled photons, a prerequisite for polarization-entangled states. Rather than directly probing entanglement, we observe the effect of hidden polarization. Our results highlight AlGaAs (111) as a promising platform for scalable quantum photonic sources and shed light on nonclassical polarization effects accessible through flat-optics engineering.
CRIS-Team Scopus Importer:2026-02-13